(untitled) (Revista dos Estudantes de Direito da Universidade de Brasília, 2023)
Whereas imparting knowledge of the law and its application remains at the heart of legal education, the emergence of Artificial Intelligence technologies is creating a shift in client needs from their lawyers, with a far grater emphasis being placed on their abilities to make best use of the information they hold, particularly in the way that they deploy influencing and negotiation skills to advance their clients’ interests. All too often, however, negotiation training courses and textbooks are little more than a series of anecdotes and situational advice. This article seeks to redress the balance by outlining both a mindset and a structure upon which any negotiation might be based. It promotes the value of curiosity, rapport-building and carefully calibrated questioning, rather than tough guy hardball demands, and it provides a five-phase model that gives a structure to a negotiation that highlights the important steps in the process and provides a foundation upon which negotiator can build their practice and skills.